Role of pessimism on the equity premium puzzle : evidence from Singapore and Malaysia - Kathiravan Arkachamy (Nanyang Technological University, 2020)
Abel (2002) demonstrated that uniform pessimism increases the objective expectation of the equity premium, thus providing an alternative solution to the equity premium puzzle presented by Mehra and Prescott (1985). In our paper, we focus on Singapore and Malaysia, where sizable equity premiums were observed. To unearth possible evidence of pessimism or optimism, median point forecasts of Gross Domestic Product (GDP) growth data from these two Southeast Asian countries were collected. We provide empirical evidence on the implication of sentiments, specifically pessimism, on asset returns in these two countries for the period 2000 to 2018. Through our analyses, we realized that forecasters from the International Monetary Fund (IMF) were generally pessimistic about Singapore and Malaysia’s output, which could have resulted in an increase in the average equity premium, thus resolving the equity premium puzzle evident in the countries. Compared to Malaysia, there was a higher level of pessimism demonstrated in the Singapore data. Governments’ aims to keep their economies away from budget deficits and rational learning from previous adversities are found to be conceivable reasons for the presence of pessimism in these two countries.